Signs of Reincarnation: Exploring Beliefs, Cases, and Theory by James Matlock - Mulacz, Peter (Journal of Scientific Exploration, 2021)
At 1606:22, Clipper 759 informed the tower that it was ready for takeoff. At 1606:24, the local controller cleared the flight for takeoff, and at 1606:30, the first officer acknowledged the clearance. The acknowledgement was the last radio transmission received from Clipper 759. On July 8, 1982, Pan American World Airways Flight 759 (Clipper 759), a Boeing 727-235, N4737, was a regularly scheduled passenger flight from Miami, Florida, to Las Vegas, Nevada, with an en route stop at New Orleans, Louisiana. About 1607:57 central daylight time, Clipper 759, with 7 crewmembers, 1 nonrevenue passenger on the cockpit jumpseat, and 137 passengers on board, began its takeoff from runway 10 at the New Orleans International Airport, Kenner, Louisiana. At the time of flight 759’s takeoff, there were showers over the east end of the airport and to the east end of the airport along the airplane’s intended takeoff path. The winds at the time were gusty, variable, and swirling. Clipper 759 lifted off the runway, climbed to an altitude of between 95 feet to about 150 feet above the ground, and then began to descend. At 1608:57, the Ground Proximity Warning System (GPWS) activated and “Whoop whoop pull up whoop. . . .” was recorded. The airplane struck a line of trees about 2,376 feet beyond the departure end of runway 10 at an altitude of about 50 feet above the ground. The airplane continued on an eastward track for another 2,234 feet hitting trees and houses and then crashed into a residential area about 4,100 feet from the end of the runway. The airplane was destroyed during the impact, explosion, and subsequent ground fire. One hundred forty-five persons on board the airplane and eight persons on the ground were killed in the crash. Six houses were destroyed; five houses were damaged substantially.1,2 Moreover, nine people on the ground suffered severe injuries. The aircraft hit the ground with a considerable left bank angle, firstly hitting an oak tree with the left wing, cutting the power and the telephone lines mounted on poles, then destroying the houses of the Schultz family, the neighboring house, and a few others, and eventually cartwheeled and broke into pieces. Kerosene spilled from the ruptured tanks and ignited although there was a thunderstorm with heavy rain; three members of the Schultz family staying in their house were badly burned, one of them died in hospital. Among those killed on the ground—actually the first victim along the swathe of destruction caused by the crashing/impacting aircraft—was Jennifer Schultz, then eleven years of age, who was in the carport (perhaps was talking on the telephone, sitting on a swing there as she used to do) when disaster struck. On March 11th, 2008, in Bartlesville, Oklahoma, a girl, Rylann, was born to the O’Bannion family. Rylann appeared to be developing earlier than usual, but she showed some curious habits, e.g., for some time she kept sleepwalking. She started complaining that her hair touching her back hurt her back; she drew dramatic fits about putting on shirts. The clothing, she would complain, hurt her back, neck, and shoulders—it felt like her skin was burning. Referring to a photograph she mentioned time and again, she had been “bigger” than on that picture, a statement that didn’t make sense to her mother at that point in time. Eventually, at the age of three years and five months, again touching the topic of having been “bigger” before, she said: “Mommy, I died. I was in our backyard. It was raining. I was alone but I wasn’t scared. Then the rain shocked me. It was raining a lot. There was a loud noise, then the rain shocked me. I floated up to the sky then.” As the O’Bannion family subscribed to the Catholic faith, reincarnation was not a subject to consider. Over time, Rylann added new bits of memory; at the age of five she started talking about what happened to her “in heaven” after her death (meeting God and Jesus, and ‘Grandy Sally’ whom she never had met in reality), and that “you can choose to come back if you died before you were supposed to.” Once, out of the blue, she said “I remember the name of Jennifer.”